The effect of user-generated content on tourist behavior: the mediating role of destination image - Alcázar,María del Carmen Hidalgo (2014)
The importance of the Internet on the image formation process has been widely recognised by both academic and practitioners. Despite the increasing use of user-generated electronic content as an information source for tourists, its influence on destination image formation is not yet fully understood. In order to bridge this knowledge gap in tourism management, we conducted an empirical study to identify the impact of online user generated reviews on the two dimensions of destination image: affective and cognitive. The results of this study extend previous works by demonstrating how user-generated content affects the image of a tourist destination. This study also analyses the mediating effects of the cognitive and affective dimensions of destination image on behavioural intentions.